Taguchi design and flower pollination algorithm application to optimize the EMI shielding of plaster mortar containing palm oil fuel ash - Oh Lai Ching, Narong; Sia, Chee Kiong; Yee, See Khee; Ong, Pauline; Zainudin, Azlan; Muhd Nor, Nik Hisyamudin; Hassan, Mohd Fahrul (International Journal of Integrated Engineering, 2018)
To solve the electromagnetic interference (EMI) radiation issue, the palm oil fuel ash (POFA) was used as a cement replacement in wall plastering application for mitigating against the electromagnetic wave (EMW). The variables involved POFA admixture percentage (weight%), topcoat powder-to-binder ratio, water-to-binder ratio, latex agent content (weight%), particle size of POFA (µm) and curing conditions. Besides, the EMI shielding effectiveness (SE) is mainly dependent on all variables, especially POFA admixture percentage and particle size of POFA. A hybrid Taguchi design and flower pollination algorithm (FPA) method was used to optimize the best approaching high EMI SE based on experimental data. The experimental investigation was found that plaster cement can shield -23dB of EMW while FPA can achieve -24.68dB. The interaction model of EMI SE was derived from regression analysis and found that the EMI SE is dependent on the water-to-binder ratio followed by latex agent content, particle size of POFA and curing conditions. From the FPA process, targeted EMI SE approaching high values were predicted for 30.012% of POFA admixture percentage, 0.3 of topcoat powder-to-binder ratio, 1.03 of water-to-binder ratio, 10% of latex agent content, 45µm particle size of POFA and air curing condition.